Теория катастроф и управление рисками в технических системах критического назначения - Набивач, В. Е. (Видавництво Львівської політехніки, 2011)
Applications of catastrophe theory are considered from the perspective of a risk management in technical systems. We considered the space of critical parameters and singularity manifolds on them that limit the unimodal systems. From the viewpoint of singularity theory are considered the issues of risk management in multichannel transport systems and to improve the reliability of space-critical applications.
Keywords: сatastrophe theory; risk management; singularity manifolds